Pronoun, Personal Titles, and Variety of Java-Indonesian Language in Yowis Ben The Series Film: Contrastive Study - Prastiyono, Yustri Agung; Fahmilda, Yacub; Latief, Suryawahyuni (Anglophile Journal, 2021)
This study aimed to identify and to contrast differences in Javanese-Indonesian speech acts in the Yowis Ben The Series film. This study used a contrastive analysis study with a sociolinguistic approach, which in this context emphasizes the aspects of pronouns, personal titles, and language variations. The method used in this research was descriptive qualitative. The data in this study are speech acts in Javanese and Indonesian (translation) which are used as dialogues in the film. The data source in this study was taken from the Yowis Ben The Series film through the WeTV video streaming application. The results of this study indicated that there were differences usage of Javanese-Indonesian speech in aspects of pronouns, personal titles, and language variations. This difference was due to non-linguistic aspects, such as the speaker's background, age, position or degree of speech partners in society. Keywords: Speech Act, Contrastive Analysis, Sociolinguistic